O estatuto contemporâneo dos códigos informáticos: o "copiar e colar" e a organização do pensamento na sociedade tecnológica - Moura, Giovani Pagliusi Lobato e (2012)
This Masters Dissertation proposes to analyze the compound command copy and paste of the operational keyboard. Mapping the factors involved in the procedure contextualizes its origins, its main aspects, and the way in which copy and paste plays an important role in shaping and organizing thought in today s society through the convergence of communication and information technologies. The scope of this investigation, of a solely theoretical nature, comprises examples that do not include digital networks, thus enabling us to recognize some of the features of copy and paste that are not exclusively part of the current interactive movement. A strategic presentation of copy and paste in the cybercultural domain is then introduced as a potentiating instrument of behavior that leads to thinking along the lines of current virtual patterns. The research problem consists of the following questions: What are the factors that favor the inclination to use this command? Can a person use copy and paste as a factor of accessibility that suggests a kind of thinking unlike the other existing types? Or does copy and paste propose a shortcut whereby some categories of thought are suspended in favor of others? What are these categories? As its primary hypothesis, this study considers that thought is transformed insofar as social relations tend towards a necessarily instrumental and hybrid perspective endorsed by emergent technological discoveries. The study materializes a theoretical reflection about the possible changes that thinking undergoes when using copy and paste resources. The routes that are followed here propose the existence of a thought process parallel to traditional discursive thought. A type of thinking driven by rapid and image-related strategies emerges in the relationship between the subject and computing processes, based on simplifying aspects that favor a considerably more contemplative reflection of the object. It is a thought process that has developed from a civilizatory logic in which evolutionary patterns must be considered that simultaneously involve the current status of society, of history and of the subject. Since there is no specific theory about cyberspacerelated operational commands, the rationale of this research focused on theoretical proposals founded upon the category of critique consolidated in the last few decades, based on the following authors: Jean-François Lyotard, Fredric Jameson and Krishan Kumar (postmodernity), Paul Virilio (dromology), Eugênio Trivinho (cybercultural dromocracy), Philippe Breton (communication as a utopistic value), Flusser (surface thinking) and Jean Baudrillard (consumption and excess)